The enhancing effect of Acanthopanax sessiliflorus fruit extract on the antibacterial activity of porcine alveolar 3D4/31 macrophages via nuclear factor kappa B1 and lipid metabolism regulation - Hwang, Eunmi; Kim, Gye Won; Song, Ki Duk; Lee, Hak-Kyo; Kim, Sung-Jo (Animal bioscience, 2019)
Objective: The demands for measures to improve disease resistance and productivity of livestock are increasing, as most countries prohibit the addition of antibiotics to feed. This study therefore aimed to uncover functional feed additives to help enhance livestock immunity and disease resistance, using Acanthopanax sessiliflorus fruit extract (ASF). Methods: ASF was extracted with 70% EtOH, and total polyphenolic and catechin contents were measured by the Folin-Ciocalteu and vanillin assay, respectively. The 3D4/31 porcine macrophage cells (M[PHI]) were activated by phorbol 12-myristate 13-acetate (PMA), and cell survival and growth rate were measured with or without ASF treatment. Flow-cytometric analysis determined the lysosomal activity, reactive oxygen species levels (ROS), and cell cycle distribution. Nuclear factor kappa B (NF-[kappa]B) and superoxide dismutase (SOD) protein expression levels were quantified by western blotting and densitometry analysis. Quantitative polymerase chain reaction was applied to measure the lipid metabolism-related genes expression level. Lastly, the antibacterial activity of 3D4/31 M[PHI] cells was evaluated by the colony forming unit assay. Results: ASF upregulated the cell viability and growth rate of 3D4/31 M[PHI], with or without PMA activation. Moreover, lysosomal activity and intracellular ROS levels were increased after ASF exposure. In addition, the antioxidant enzyme SOD2 expression levels were proportionately increased with ROS levels. Both ASF and PMA treatment resulted in upregulation of NF-[kappa]B protein, tumor necrosis factor (TNF)[alpha] mRNA expression levels, lipid synthesis, and fatty acid oxidation metabolism. Interestingly, co-treatment of ASF with PMA resulted in recovery of NF-[kappa]B, TNF[alpha], and lipid metabolism levels. Finally, ASF pretreatment enhanced the in vitro bactericidal activity of 3D4/31 M[PHI] against Escherichia coli. Conclusion: This study provides a novel insight into the regulation of NF-[kappa]B activity and lipid metabolism in M[PHI], and we anticipate that ASF has the potential to be effective as a feed additive to enhance livestock immunity. Keywords: Porcine; Feed Additives; Acanthopanax sessiliflorus; Macrophages; Nuclear Factor Kappa B (NF-[kappa]B); Immunity